Problem Posing: Creative Thinking Ability-Based Theory Wallas from Habits of Mind - Dewi Pratiwi, Febria; Mardiyana; Pramudya, Ikrar (Education, Science, and Technology International Conference, 2024)
This qualitative research aimed to analyze and delineate the stages of creative thinking as per Wallas' theory, observed through students' problem-posing abilities categorized by habits of mind. The research employed questionnaires, problem posing tasks, and interviews to explore how students in developing and proficient habits of mind categories demonstrate creative thinking in problem-posing. The instruments included a questionnaire on thinking habits and assessments of problem-posing skills. Subjects were purposively selected based on their classification into three habits of mind categories. Data analysis involved techniques of data reduction, presentation, and drawing conclusions. The findings revealed distinct behaviours: students with developing habits of mind tend to propose new problems under familiar conditions without error correction. In contrast, those classified with proficient habits of mind propose new problems under varied conditions and effectively address errors. Other subjects exhibit behaviours intermediate between these categories, problem-posing similarly and rectifying errors as necessary.